BLOOD PRESSURE CORRELATION WITH IN-HOSPITAL MORTALITY ST-ELEVATION MYOCARDIAL INFARCTION PATIENT CASE STUDY IN RSUP DR. KARIADI - Agung Satria Winahyu; Ilham Uddin; Sefri Noventi Sofia; Ariosta Ariosta (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Blood pressure had been suspected to correlate with in-hospital mortality on ST-Elevation Myocardial Infarct (STEMI) patients. Aim: To prove the correlation between blood pressure with short-term in-hospital mortality on STEMI patients. Methods: This study was a retrospective analytic observational qualitative study with a cohort design. The data collecting technique used STEMI patient medical records at the RSUP dr. Kariadi and took blood pressure data when the patients admitted to the hospital, after that divided into three groups, namely hypertension, normotension, and hypotension, then analyze the data on the output of patients alive or dying when they were discharged from the hospital using Fisher exact test.  Results: Hypertension (p=0,428; OR=0,355), Normotension (p = 1; OR=1,267), and Hypotension (p=0,687; OR=1,500) along with hypertension history (p=0,785; OR=1,200) was not correlated with in-hospital mortality of STEMI patient in RSUP dr. Kariadi.  Conclusion: There was no correlation between blood pressure at admission with in-hospital mortality in STEMI patients.